The importance of indirect losses in the seismic risk assessment of industrial buildings – An application to precast RC buildings in Portugal. (May 2022) - Sousa, R.; Silva, V.; Rodrigues, H.
Abstract: Observations from past destructive earthquakes indicate that indirect economic losses can greatly exceed the direct economic losses. However, the influence of indirect losses is often neglected in seismic risk studies due to the complexity associated with their evaluation, as well as the fact that direct losses tend to gather public attention due to human losses and the visual impact of structural damage. This issue is particularly evident in the assessment of indirect losses linked to industrial activities, which can represent a significant portion of the economy. The present study presents a comprehensive framework for the assessment of indirect economic losses based on the impact of business interruption and interdependency between the different economic sectors. The application of the proposed model to precast reinforced concrete buildings constitutes the first seismic risk study of this typology in Portugal, and highlights the critical need to pursue risk mitigation measures to address both the potential direct and indirect effects in the Portuguese economy.